Alkali and alkaline earth coordination polymers constructed from benzene‐1, 2, 4, 5‐tetracarboxylic acid and flexible dicarboxylate acid ligands: syntheses, structures and spectroscopic and thermal properties. Issue 2 (14th January 2021) - Lifa, Said; Trifa, Chahrazed; Bouacida, Sofiane; Boudaren, Chaouki; Merazig, Hocine
Abstract : Two new alkali/alkaline earth coordination polymers were prepared from benzene‐1, 2, 4, 5‐tetracarboxylic acid as a rigid polycarboxylate metal linker and two types of flexible dicarboxylate ligands as the second linker under similar hydrothermal reaction conditions. The polymers were structurally characterized by single‐crystal X‐ray diffraction. The flexible dicarboxylate ligands play an important role in tuning the detailed structures and characteristics of the complexes. Abstract : Two new metal coordination complexes, namely, poly[aqua(μ6 ‐benzene‐1, 2, 4, 5‐tetracarboxylic acid‐κ 8 O 1 : O 1, O 2 : O 2′ : O 4 : O 4, O 5 : O 5′ )(μ‐but‐2‐enedioato‐κ 2 O 1 : O 4 )potassium(I)], [K2 (C4 H2 O4 )(C10 H6 O8 )(H2 O)2 ] n or [K2 (fum)(H4 btec)(H2 O)2 ] n, (1), and poly[aqua(μ8 ‐2, 5‐dicarboxybenzene‐1, 4‐dicarboxylato‐κ 12 O 1 : O 1′, O 2 : O 2, O 2′ : O 2′ : O 4 : O 4′, O 5 : O 5, O 5′ : O 5′ )(μ‐ethanedioato‐κ 4 O 1, O 2 : O 1′, O 2′ )strontium(II)], [Sr2 (C2 O4 )(C10 H4 O8 )(H2 O)2 ] n or [Sr2 (ox)(H2 btec)(H2 O)2 ] n, (2) (H4 btec = benzene‐1, 2, 4, 5‐tetracarboxylic acid, H2 btec = 2, 5‐dicarboxybenzene‐1, 4‐dicarboxylate, fum = fumarate and ox = oxalate), have been obtained under hydrothermal conditions by reacting the different alkali and alkaline earth metal salts with H4 btec, fumaric acid (H2 fum) and oxalic acid (H2 ox). Complexes (1) and (2) were structurally characterized by single‐crystal X‐ray diffraction, IR and UV–Vis spectroscopy, powder X‐ray diffraction (PXRD) and thermogravimetic analysis–differential scanning calorimetry (TGA–DSC). Complex (1) displays a two‐dimensional (2D) layer with the K + ion in a distorted pentagonal bipyramidal geometry and exhibits a uninodal 6‐connected hxl/Shubnikov plane net (3, 6) with {3 6 .4 6 .5 3 } topology. Complex (2) displays a three‐dimensional (3D) network structure, in which the Sr 2+ ion is in a distorted monocapped square antiprism geometry. The framework possess a binodal (5, 8)‐connected net with the Schläfli symbol {3 2 .4 10 .5 8 .6 4 .7 4 }{3 2 .4 6 .5 2 }2 . The 3D Hirshfeld surfaces and 2D fingerprint plots show that the main interactions are the O…H/H…O intermolecular interactions. Moreover, the thermal decompositions of (1) and (2) in the temperature range 303–1273 K revealed that they both decompose in three steps and transform to the corresponding metal oxide.